Elliptic Curve Cryptography Services for Mobile Operating Systems - Figueira, Ana Raquel Correia (2015)
Mobile devices as smartphones, tablets and laptops, are nowadays considered indispensable objects by most people in developed countries. A s personal and work assistant s , some of th e s e devices store , process and transmit sensitive and private data. Naturally , the number of mobile applications with integrated cryptographic mechanisms or offering security services has been significantly increasing in the last few years. Unfortunately, not all of those applications are secure by design, while other may not implement the cryptographic primitives correctly. Even the ones that implement them correctly may suffer from longevity problems, since cryptographic primitives that are considered secure nowadays may become obsolete in the next few years. Rivest, Shamir and Adleman (RSA) is an example of an widely used cryptosystem that may become depleted shorty . While the security issues in the mobile computing environment may be of median severity for casual users, they may be critical for several professional classes, namely lawyers, journalists and law enforcement agents. As such, it is important to approach these problems in a structured manner. This master’s program is focused on the engineering and implementation of a mobile application offering a series of security services. The application was engineered to be secure by design for the Windows Phone 8.1 Operating System (OS) which, at the time of writing this dissertation, was the platform with the most discreet offer in terms of applications of this type. The application provides services such as secure exchange of a cryptographic secret, encryption and digital signature of messages and files, management of contacts and encryption keys and secure password generation and storage. Part of the cryptographic primitives used in this work are from the Elliptic Curve Cryptography (ECC) theory, for which the discrete logarithm problem is believed to be harder and key handling is easier. The library defining a series of curves and containing the procedures and operations supporting the ECC primitives was implemented from scratch, since there was none available, comprising one of the contributions of this work. The work evolved from the analysis of the state-of-the-art to the requirements analysis and software engineering phase, thoroughly described herein, ending up with the development of a prototype. The engineering of the application included the definition of a trust model for the exchange of public keys and the modeling of the supporting database. The most visible outcomes of this master’s program are the fully working prototype of a mobile application offering the aforementioned security services, the implementation of an ECC library for the .NET framework, and this dissertation. The source code for the ECC library was made available online on GitHub with the name ECCryptoLib [Ana15]. Its development and improvement was mostly dominated by unit testing. The library and the mobile application were developed in C?. The level of security offered by the application is guaranteed via the orchestration and combination of state-of-the-art symmetric key cryptography algorithms, as the Advanced Encryption Standard (AES) and Secure Hash Algorithm 256 (SHA256) with the ECC primitives. The generation of passwords is done by using several sensors and inputs as entropy sources, which are fed to a cryptographically secure hash function. The passwords are stored in an encrypted database, whose encryption key changes every time it is opened, obtained using a Password-Based Key Derivation Function 2 (PBKDF2) from a master password. The trust model for the public keys designed in the scope of this work is inspired in Pretty Good Privacy (PGP), but granularity of the trust levels is larger.